Medida da magnetização de filmes finos: desenvolvimento de um magnetômetro kerr - Garcia, Wagner Jesus da Silva (2014)
The Kerr effect is the rotation of the plane of polarization of a light beam during reflection on a magnetized sample. In this work we built an optical Kerr effect magnetometer Longitudinal (L-MOKE) and measured the magnetization of thin films produced by the technique of "magnetron sputtering". The magnetization measurements were in samples of permalloy (Py), iron (Fe) and a tri-layer Py/IrMn/Ta.